2012
DOI: 10.1111/j.1365-2869.2012.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Holland Sleep Disorders Questionnaire: a new sleep disorders questionnaire based on the International Classification of Sleep Disorders‐2

Abstract: SUMMARYThe primary objectives of this study were to construct a self-assessment questionnaire for sleep disorders based on the International Classification of Sleep Disorders-2, and to evaluate the questionnaireÕs psychometric properties with respect to its total score and the individual scores for each of the six sleep disorders. In total, 1269 patients, clinically diagnosed with a sleep disorder, and 412 subjects without sleep complaints were enrolled into this study. Principal components analysis confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 9 publications
3
81
1
Order By: Relevance
“…This was higher than the 20% found by Zak (Kerkhof et al, 2013). (Kerkhof et al, 2013); RLS: restless legs syndrome; PLMD: periodic limb movement disorder; ADHD-RS: ADHD-Rating Scale (DuPaul et al, 1998;Kooij et al, 2005)) 6 SNITSELAAR, SMITS, SPIJKER et al (2009) and even higher than we expected in our hypothesis, based also on literature about childhood ADHD. The prevalence of RLS and RLS symptoms was higher in the ADHD-C type group compared with the ADHD-I group, although the difference was not significant.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…This was higher than the 20% found by Zak (Kerkhof et al, 2013). (Kerkhof et al, 2013); RLS: restless legs syndrome; PLMD: periodic limb movement disorder; ADHD-RS: ADHD-Rating Scale (DuPaul et al, 1998;Kooij et al, 2005)) 6 SNITSELAAR, SMITS, SPIJKER et al (2009) and even higher than we expected in our hypothesis, based also on literature about childhood ADHD. The prevalence of RLS and RLS symptoms was higher in the ADHD-C type group compared with the ADHD-I group, although the difference was not significant.…”
Section: Discussioncontrasting
confidence: 64%
“…The cutoff score for RLS/PLMD is 2.70. In Receiver Operating Characteristic (ROC) curve analysis, the discriminating performance for the RLS/PLMD subscale obtained a score of 4 SNITSELAAR, SMITS, SPIJKER 0.887 for the P(A) measure of overall accuracy (Kerkhof et al, 2013). Consequently, the sleep disorder diagnoses in this study were based on the outcomes of the HSDQ and were not confirmed with clinical data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Exclusion criteria were (1) suicidal intentions and drug abuse, investigated through clinical scores and item screening on the Youth Self Report (YSR) 38,39 and from the intake interview, (2) indication of other sleep disorders than insomnia indicated by scores above cutoff on the HSDQ and through information from the intake interview, (3) a diagnosis of other psychological disorders (e.g. depression, ADHD), or presently being treated for psychological or sleep problems, (4) use of drugs or medication that interfere with sleep, or (5) a lack of chronicity or severity of the symptoms according to the DSM-5 criteria for insomnia disorder 36 as indicated in the one hour face to face diagnostic intake interview.…”
Section: Participantsmentioning
confidence: 99%